Moderate vs heavy strength training: what is best for long distance triathlon performance? - Baldwin-Luckin, K. M.; Badenhorst, C.; Cripps, A.; Merrells, R.; Bulsara, M.; Hoyne, G. (Journal of Australian Strength and Conditioning, 2019)
A progressive strength training program transitioning from moderate to heavy loads may be used to improve performance in long-distance triathletes.